Greening sustainable supply chain performance: The moderating and mediating influence of green value co-creation and green innovation - Banji Rildwan Olaleye; Sara Faysal Mosleh (Administrative Sciences, 2025)
This paper aimed to analyze the effect of green supply chain integration (GSCI) on sustainable supply chain performance (SSCP), as well as consider the mediating and moderating effects of green innovation (GInv) and green value co-creation (GVCc). This empirical study is based on a survey of 317 senior managers from agro-based companies involved in manufacturing and extractive industries in Nigeria. The empirical research model is examined utilizing partial least squares structural equation modeling (PLS-SEM). The discovery entails that GSCI positively and substantially impacted SSCP and GInv. The research suggests that green innovation serves as a mediator in the relationship between GSCI and SSCP. Moreover, green value co-creation exerts a detrimental moderating influence on the GSCI-SSCP paradigm. Meanwhile, the originality of this study emanated from being the first to objectively explore the simultaneous moderating and mediating effects of GInv and GVCc on the relationship between GSCI and SSCP.
Keywords: 350; green value co-creation; green supply chain integration; green innovation; partial least squares structural equation modeling; sustainable supply chain performance